2016
DOI: 10.1111/jfpe.12373
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Corn Drying in a Hybrid Fluidized Bed‐Infrared Dryer

Abstract: This study deals with numerical modeling and experimental validation of hybrid fluidized bed-infrared drying of bulk grain. A mathematical model of simultaneous heat and mass transfer for the aforementioned dryer was developed: first single phase model was used to establish heat and mass transfer equations over the fluidized bed, then the effect of infrared heating was incorporated into the single phase model as a source term to develop the model for a hybrid fluidized bedinfrared dryer. The model is capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The hybrid infrared-convective drying produces a synergistic effect, and is therefore considered to be more efficient than individual IR or convection drying methods [5]. It has been extensively applied on different products, including sweet potato [6] and kiwifruit [7].…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid infrared-convective drying produces a synergistic effect, and is therefore considered to be more efficient than individual IR or convection drying methods [5]. It has been extensively applied on different products, including sweet potato [6] and kiwifruit [7].…”
Section: Introductionmentioning
confidence: 99%
“…CFD simulation has become a useful tool for solving modern fluid engineering problems (Villermaux, 2019). For example, Nejadi and Nikbakht (2017) established a CFD model of simultaneous heat and mass transfer for the hybrid fluidized bed-infrared drying of bulk grain, which indicated acceptable performance and hence the CFD model could be a scientific tool providing precise prognostications dealing with fluidized bed drying. Ramachandran, Akbarzadeh, Paliwal, and Cenkowski (2017) conducted CFD modeling for superheated steam drying of spent grain pellet.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemical pretreatments hold the problems of chemical additives residue (Bai, Sun, Xiao, Mujumdar, & Gao, 2013). Several nonchemical treatment methods for drying have been devised over the past decade, such as the infrared, ultrasound, microwave, superheated steam, and their combinations (Lv, Zhang, Wang, & Adhikari, 2018;Momenzadeh, Zomorodian, & Mowla, 2011;Moraitis & Akriridis, 1998;Nejadi & Nikbakht, 2017). Nejadi and Nikbakht (2017) reported that hybrid fluidized bed-infrared drying of corn led to a 45 -87% saving in drying time.…”
mentioning
confidence: 99%
“…Several nonchemical treatment methods for drying have been devised over the past decade, such as the infrared, ultrasound, microwave, superheated steam, and their combinations (Lv, Zhang, Wang, & Adhikari, 2018;Momenzadeh, Zomorodian, & Mowla, 2011;Moraitis & Akriridis, 1998;Nejadi & Nikbakht, 2017). Nejadi and Nikbakht (2017) reported that hybrid fluidized bed-infrared drying of corn led to a 45 -87% saving in drying time. Abdoli, Zare, Jafari, and Chen (2018) showed that ultrasound frequency of 25 kHz and power density 14.6 kW m −3 on fluidized bed drying of corn caused 43% reduction in drying time.…”
mentioning
confidence: 99%